Audit Sistem Informasi Aplikasi Payroll Management System Menggunakan Framework COBIT 5 - Annisa Rahmadiah; Eva Zuraidah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Payroll Management System (PMS) is an application used by Ministry of Foreign Affairs of Indonesia as a solution to their problem on performance allowance payment process for their employees to be more effective and efficient, as well as to avoid errors and fraud when processing data. In this application, inputting data proposals by the work unit admin must go through a verification process from the super admin in the human resources bureau, and in terms of verifying the proposal, it must be free from errors. This research is based on a qualitative method, and the results were analyzed by framework COBIT 5 with DSS (Deliver, Support, System) as a chosen domain, especially DSS01 manage operations and DSS02 manage service requests and incidents. The results showed that maturity value index of each process complied with all available stages. Maturity level results on domain DSS01 showed that it has maturity level 11,43 out of desired level 4 with achievement value fully achieved, GAP value was 7,43, and achieved level of optimizing process on IT capability, while domain DSS02 showed maturity level on 8,20 out of desired level 4 with achievement value fully achieved, GAP value was 4,20, and achieved level of optimizing process. It can be concluded that Payroll Management System (PMS) has reached beyond the maximum capacity level